2004
DOI: 10.1182/blood-2004-02-0715
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel mutations in ADAMTS13 in an adult patient with congenital thrombotic thrombocytopenic purpura

Abstract: Congenital thrombotic thrombocytopenic purpura/hemolytic uremic syndrome (TTP/HUS) is associated with an inherited von Willebrand factor-cleaving protease (ADAMTS13 [a disintegrin and metalloprotease with thrombospondin type I domains 13]) deficiency. In this study, we identified novel mutations in the ADAMTS13 gene in a patient with TTP. The patient was a 51-year-old Japanese male who exhibited TTP symptoms at frequent intervals. The ADAMTS13 activity during acute episodes was less than 3% that of normal. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 24 publications
0
49
0
1
Order By: Relevance
“…These and subsequent studies demonstrate that inhibitory autoantibodies are detectable in most patients with acquired TTP (32). Furthermore, following the first study linking hereditary TTP to mutations of the ADAMTS13 gene (4), other studies have identified more mutations in patients with the disease (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Together these two lines of evidence confirm that ADAMTS13 deficiency plays a pivotal role in causing the VWFplatelet thrombosis of TTP.…”
Section: Adamts13 Deficiency and Ttpmentioning
confidence: 86%
See 1 more Smart Citation
“…These and subsequent studies demonstrate that inhibitory autoantibodies are detectable in most patients with acquired TTP (32). Furthermore, following the first study linking hereditary TTP to mutations of the ADAMTS13 gene (4), other studies have identified more mutations in patients with the disease (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Together these two lines of evidence confirm that ADAMTS13 deficiency plays a pivotal role in causing the VWFplatelet thrombosis of TTP.…”
Section: Adamts13 Deficiency and Ttpmentioning
confidence: 86%
“…DNA nucleotide sequence analysis has detected at least 9 nonsense, 42 missense, 9 frameshifting insertion or deletion, and 6 splicing mutations (4,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). These mutations span the entire length of the protein without apparent hot spots.…”
Section: Vwf Multimer and Proteolytic Fragmentsmentioning
confidence: 99%
“…Inherited TTP is a rare autosomal recessive disorder due to homozygous or double heterozygous mutations in the ADAMTS-13 gene, causing a severe decrease of ADAMTS-13 level and activity (10)(11)(12)(13)(14)(15)(16). About 100 mutations causing inherited ADAMTS-13 deficiency have been identified so far in regions of the gene encoding different domains (10)(11)(12)(13)(14)(15)(16)(17) with only a few of them characterized by in vitro expression studies (12,15,(18)(19)(20)(21)(22). In this manuscript, we report cases of congenital TTP, due to the homozygous mutation in ADAMTS-13 gene in two young brothers born from two consanguineous parents of Romanian origin.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] The present study evaluates the molecular mechanism of two mutations observed in the compound heterozygous state in two Turkish siblings with congenital TTP. One mutation, present on the maternal allele, is a single base (A) insertion mutation located within exon 29 (c.4143_4144insA) in the second CUB domain, leading to a frameshift and loss of the last 49 amino acids of the protein.…”
Section: Introductionmentioning
confidence: 99%